Single‐Cell RNA Sequencing Reveals the Temporal Diversity and Dynamics of Cardiac Immunity after Myocardial Infarction. Issue 3 (13th January 2022) - Jin, Kaiyu; Gao, Shan; Yang, Penghui; Guo, Rongfang; Li, Dan; Zhang, Yunsha; Lu, Xiaoyan; Fan, Guanwei; Fan, Xiaohui
Abstract: Myocardial infarction (MI) is strongly associated with the temporal regulation of cardiac immunity. However, a variety of current clinical trials have failed because of the lack of post‐MI immunomodulating/anti‐inflammatory targets. Single‐cell RNA sequencing analysis of the cardiac Cd45 + immune cell at 0, 3, 7, and 14 d after injury in a mouse left anterior descending coronary artery ligation model is performed. Major immune cell populations, distinct subsets, and dynamic changes are identified. Macrophages (Mø) are most abundant, peaking at 3 d after infarction. Mø‐5 and Mø‐6 are the predominant infiltrated subsets at this time point, with strong expression of inflammatory factors. Further analysis demonstrates that suppressing these sets attenuated pathological MI progression by preventing subsequent leukocyte extravasation and adverse remodeling. Abundant apoptotic neutrophils and a profibrotic macrophage subset on days 7 and 14, respectively, are also detected. These results provide a basis for developing cell type‐ and time‐specific interventions in MI. Abstract : Temporal regulation of cardiac immunity is strongly associated with the onset, progression, and outcomes of myocardial infarction (MI). The study of time‐series scRNA‐seq on the whole cardiac immune cells isolated from the left anterior descending coronary artery ligation mice and the tanshinone IIA‐treated mice sheds light on the underlying pathology of MI.